Organic vs. conventional : comparative study on pollinating insects and their efficiency in white clover fields - Johansson, Szilvia (SLU/Dept. of Plant Breeding (from 130101), 2017)
Agricultural intensification has altered our environment, and many natural habitats for living organisms have been altered or completely disappeared. To restore and conserve biological systems while keeping the food supplies on an acceptable level, there is a demand for organic practice in the agriculture sector. 75 % of the plants for human consumption and animal forage are dependent on animal pollination therefor it is equally important to increase the variety of the cultivated plants and find sustainable solution that is relatively cheap to grow. Due to its special characteristics (nitrogen fixing ability, highly adaptable to abiotic factors) white clover seem to be a good solution. It provides excellent forage for grazing animals and moreover for pollinating insects. There have been many studies conducted to find out what the most important factors are which could give a satisfactory yield by the least effort and least financial investment. There is an ongoing high-tempered discussion whether it is possible to maintain the harvested seed level without chemical pest control. To find more insight, this study was carried out on both organically (7 fields) and conventionally (6 fields) managed fields in the southern part of Sweden. All the fields were designated for seed production. This study includes 3 surveys on pollinator abundance and diversity regarding white clover pollinating insects. Measurements were taken and recorded on abiotic (sun dominance, wind strength, temperature) and biotic factors (number of blooming white clover flowers, number of florets/flower head, number of seeds 2 weeks after the surveys) and landscape characteristics (field borders, other landscape element edges, flowering crops, land use diversity). The study aim was to investigate how pollination activity and pollination effectiveness differs between the two farming systems and to find factors that explain the results. The results showed that there was a significant difference between the amounts of visiting pollinators, benefiting the conventionally managed fields. Among the abiotic factors, temperature had the strongest effect on the pollination activity. There was a positive correlation between the amount of honey bees and the amount of bumblebees and wild pollinators. With regards to landscape characteristics, the investigation showed that honey bees (A. mellifera) abundance negatively correlated with the area of field borders and landscape element edges within the 2 km and 3 km buffer zone. Wild bee abundance negatively correlated with the Simpson land use diversity index within the 2 and 3 km buffers zones. However, the seed production and the pollinator abundance showed no correlation. Conclusively, there is an interesting connection to follow up with regards to landscape features and the amount of pollinators and other effecting factors.